A beginner's guide to the world of investments (New York, 1995)
The book purposes on today's world money management that introduces the novice to the many facets of investments in simple: bonds, securities, insurance, mutual funds, the stock market, real estate, options, retirement and estate planning, employee benefits...
Keywords: Estate planning,Finance, personal,Investments,Mutual funds,Securities